Empire in the mirror of geopolitics - Aleksandr Aseev; Vasilii Shishkov (Управление)
The article deals with the geopolitical views of the Empire as a special type of state and politics, the laws of its development and the place of the Empire in the theoretical constructions of modern geopolitics. The Empire appears to be a large-scale expansionist, geopolitically self-sufficient political entity. While in geopolitics are traditionally distinguished continental (tellurocracy) and sea (thalassocracy) Empires. Studies in the framework of the geopolitical approach fixate, that the extensive path of Imperial power entails a lack of resources to maintain the Imperial system, which has reached its maximum limits by this time. The crisis, linked with Imperial tension, marks the limit of Imperial expansion, followed by the collapse of the Empire into several smaller political entities. In the geopolitical aspect, the Empire-state is in close connection with the aspirations to dominate not only the subordinate periphery, but also other less important and powerful participants in international politics. The ability of the Empire to act as a center of power can be considered as one of its сharacteristics. In general, the geopolitical interpretation of the Empire allows us to point to its specifics, but not as a state, but as a special type of policy, aimed at establishing dominance by the content, which is the concentration of political resources and the exclusive position of the state, forming the Imperial center. Geopolitical analysis emphasizes the central position of the Imperial metropolis in the coordinates of the center–periphery relations, on the one hand, acting as a source of political guidelines and rules, on the other hand, the concentration of political resources and monopolistic political position, provided, among other things, by superiority in geopolitical positioning due to long-term strategic planning and policy.